Observaciones ecológicas sobre el pez capitán, eremophilus mutisii humboldt 1805 (pisces: trichomycteridae) en los departamentos de cundinamarca y boyacá, colombia (1989)
Information of the population for several Eremophilus muusu Humboldt 1805 were provided at the Cundinarnarca and Boyaca regions.The main information were concerning the habitat. dtstrtbunon of altitude. water temperature. oxygen tolerance. sizes and relation of weight/Ienght. The fertility and relation of eggs number. weight of the gonade as well the relation of reproduction index. wight of testicle. the complete weight were also gtved. On the other side conditions factor for young and adults. sex for male and female in different time of spawning were also provided.